Frictional Assignment - Shouyong Shi (Queen's University, Department of Economics, 1998)
This paper examines efficient and equilibrium allocations in an economy where agents with diverse characteristics are matched through a time-consuming process to produce output. This is cast in a labour market where workers of different skills match with machines of different qualities. The efficient assignment is not always positively assortative and can be decentralized by a competitive mechanism where firms compete by posting wages and committing to the skill that their chosen machines are intended for. Implications on wage inequality are examined.
Keywords: D33; J31; L11; 330; Matching; Efficiency; Frictions; Skills: Wage inequality